Gender Analysis In Terms Of Perception: Implementation Of The Physics-Mathematical E-Module - Astalini, Astalini; Darmaji, Darmaji; Kurniawan, Dwi Agus; Ramadhanti, Auliya (Journal of Education Research and Evaluation, 2021)
This study aims to determine whether or not there are differences in student perceptions of the Physics Mathematics I e-module product on vector material based on gender differences. This type of research is quantitative research with descriptive statistical analysis techniques and inferential analysis. The target of this research is the students of the Physics Education Study Program at the University of Jambi, class of 2019, which consists of three classes, namely Regular A, Regular B, and Regular C with a research sample of 90 students using simple random sampling. Data analysis was carried out descriptively and used normality, homogeneity, and ANOVA tests where the significance was more than or equal to 0.05. The results of the ANOVA test showed that there were differences in perceptions based on gender with a significance value of 0, 037 in women and 0.022 in men. Furthermore, in the post hoc test or Gabriel's further test, it showed that in class A and B with a significance of 0.047 for the female gender. While the male gender in class A and C has a significant difference with a significance value of 0.033. Compared to male gender, women have more dominant differences due to biological factors, where women use their emotions as opposed to men whose thoughts are more realistic.